Memperkuat Ketahanan Pangan Melalui Budidaya Hidroponik dan Tanaman Obat Keluarga (TOGA) - Ery Fatarina P; Teodora M.F.B. Da Silva; Retno Ambarwati SL; Ratna Trianingsih (Jurnal Nusantara Berbakti, 2025)
Hydroponic Cultivation and Family Medicinal Plants (TOGA) is an innovation that supports food security. The Community Service Program in Getas Village, Kendal Regency, Central Java, aims to improve agricultural land use through sustainable management and development of medicinal plants. The target of this program is for farmer groups and youth organizations. These activities include counseling, establishment of hydroponic houses, training, mentoring, monitoring, collaboration between the government and educational institutions, and evaluation and feedback. This program has succeeded in achieving several achievements, namely increasing knowledge, increasing skills, increasing production, and changing behavior.